PARTICULAR ASPECTS OF THE ORAL MUCOSA AS PREDICTIVE FACTORS FOR THE EVOLUTION OF PSORIASIS - Gabriela Stoleriu; Maria Petrescu; Ancuta Lupu; Elena Porumb Andrese; Nicuta Manolache; Daciana Elena Branisteanu (Romanian Society of Oral Rehabilitation, 2024)
Aim of the study: Psoriasis is a chronic, immune-mediated inflammatory disease primarily affecting the skin, but it can also involve the oral mucosa. Emerging evidence suggests that oral manifestations might serve as early indicators or predictive factors for psoriasis evolution. This study aims to identify specific oral mucosal features that could predict the progression and severity of psoriasis, providing insights into early diagnosis and management strategies. Materials and methods: This prospective cohort study included 150 patients with clinically and histologically confirmed psoriasis manifesting oral lesions. The exclusion criteria included other systemic inflammatory diseases, recent use of systemic immunosuppressive therapy, and inability to provide informed consent. Results: The presence of oral changes such as fissures can be directly related to patients' gender. The presence of erythema and fissures on the oral mucosa can be correlated with the severity of psoriasis disease. Conclusions: Particular aspects of the oral mucosa, including erythema, plaques, and fissures, are significant predictive factors for the evolution of psoriasis.